Spillway dam assessment using dam mass rating (Dmr) for estimating modulus of deformation and shear strength - Madun A.; Pakir F.; Md Dan M.F.; Talib M.A.; Zawawi M.H. (Books and Journals Private Ltd., 2023)
Rock mass assessment have been conducted at a spillway structure located at Sultan Mahmud power station, TasikKenyir, Kuala Berang, Terengganu, Malaysia. The assessments aim to evaluate the rock mass strength and rock deformation modulus, for investigating the stability of the spillway structure. The area of the spillway was divided into eight zones for assessment purposes which denoted as spillway zone 1 to 8. In situ rock tests were conducted including point load test, rock quality designation (RQD) and discontinuity mapping condition of rock mass as well as dam mass rating (DMR) for rating purposes. The results reveal the average of rock mass deformation modulus is 8.19 MPa and varies between 4.22 MPa and 16.79 MPa across the spillway area. From DMR value, the cohesion of rock mass ranges from 0.13 MPa to 0.24 MPa and internal friction angle from 20 to 27. The assessment at spillway also revealed that the block size is small with average of 0.013m3 with joint spacing of 0.13m. This indicates that the structure of the rock mass is highly vulnerable to break when water is flowing in high volume. On top of that, the discontinuity dip angle is dipping toward the water flow direction with uneven rock surface, which might decrease the stability of the rock mass structure in the spillway. Dam mass rating (DMR) was successfully estimated empirically the in-situ rock mass deformation modulus and shear strength of rock by using point load testing. This approach allows the engineers to make quick decisions regarding rock mass parameters if there is a sudden change in the geological structure. 2021, Books and Journals Private Ltd.. All rights reserved.